Provision of Organ at Risk Contouring Guidance in UK Radiotherapy Clinical Trials. Issue 2 (February 2020) - Yang, H.; Mir, R.; Díez, P.; Tsang, Y.; Conibear, J.; Simões, R.; Cox, S.; Webster, A.; Nabi, Z.; Eaton, D.; Naismith, O.; Whilde, N.; et al.
Abstract: Aims: Accurate delineation of organs at risk (OAR) is vital to the radiotherapy planning process. Inaccuracies in OAR delineation arising from imprecise anatomical definitions may affect plan optimisation and risk inappropriate dose delivery to normal tissues. The aim of this study was to review the provision of OAR contouring guidance in National Institute of Health Research Clinical Research Network (NIHR CRN) portfolio clinical trials. Materials and methods: The National Radiotherapy Quality Trials Assurance (RTTQA) Group carried out a two-round Delphi assessment to determine which OAR descriptions provided optimal guidance. Results: Eighty-four clinical trials involving radiotherapy quality assurance were identified as either in recruitment or in setup within the NIHR CRN portfolio. Fifty-nine trials mandated OAR contouring. In total there were 412 OAR; 171 were uniquely named; 159 OAR had more than one name associated with a single structure, with the greatest nomenclature variation seen for the femoral head ± neck, the parotid gland, and bowel. The two-round Delphi assessment determined 42 OAR descriptions as providing optimal contouring guidance. Conclusions: This study identified the need for OAR nomenclature and contouring guidance consistency across clinical trials. In response to this study and in conjunction with the Global Quality Assurance of Radiation Therapy Clinical Trials Harmonisation Group, the RTTQA Group is in collaboration with international partners to provide consensus recommendations for OAR delineation in clinical trials. Highlights: Accurate OAR contouring is vital to the radiotherapy planning process. Inaccuracies in delineation risks dose delivery to anatomical regions that are not correctly defined as part of the planning process. In response to this report, RTTQA is working with international partners to provide recommendations for OAR delineation in clinical trials.